2018
DOI: 10.1016/j.dib.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Data on the mode of binding between avenanthramides and IKKβ domains in a docking model

Abstract: The data presented in this article are related to the research paper entitled “Anti-inflammatory effect of avenanthramides via NF-κB pathways in C2C12 skeletal muscle cells.” (Kang et al., in press) [1] This article includes experimental procedures used to analyze the mode of binding between and IkB kinase (IKKβ) and avenanthramides which are a group of phenolic alkaloids found in oats. The protein-ligand docking and the computer simulation method of molecular dynamics (MD) for studying the physical interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…15 In addition, mitochondria provide local ATP to support protein synthesis required for cytoskeletal rearrangements during neuronal maturation and plasticity, 16,17 axonal regeneration through mitochondrial transport, 18 and axonal development via mitochondrial docking and presynaptic regulation. 19,20 The above-mentioned synaptic plasticity events along with neural circuits rely heavily on mitochondria-derived ATP; however, other pathways may contribute to sustain neuronal energy, including neuronal glycolysis especially during stress or high activity demands. [21][22][23] However, the balance between energy production and demand may be altered under conditions in which both accumulation of damaged mitochondria and hampered glycogenolysis/glycophagy are evident.…”
Section: Introductionmentioning
confidence: 99%
“…15 In addition, mitochondria provide local ATP to support protein synthesis required for cytoskeletal rearrangements during neuronal maturation and plasticity, 16,17 axonal regeneration through mitochondrial transport, 18 and axonal development via mitochondrial docking and presynaptic regulation. 19,20 The above-mentioned synaptic plasticity events along with neural circuits rely heavily on mitochondria-derived ATP; however, other pathways may contribute to sustain neuronal energy, including neuronal glycolysis especially during stress or high activity demands. [21][22][23] However, the balance between energy production and demand may be altered under conditions in which both accumulation of damaged mitochondria and hampered glycogenolysis/glycophagy are evident.…”
Section: Introductionmentioning
confidence: 99%
“…38 By using protein−ligand docking and the computer simulation method of molecular dynamics, AVAs (2c, 2p, 2f) were again reported to inhibit the NF-κB pathway through IKKβ due to allosteric binding. 38,39 In 2019, in a similar study on C2C12 cells, Yeo et al observed that AVAs were able to suppress TNF-α-induced muscle atrophy while also reducing proinflammatory cytokines and suppressing the NF-κB pathway. 40 Moreover, in 2020, reported by our own group, Hu and colleagues were able to characterize 15 A-type AVAs from commercial sprouted oat products and observed their health-promoting benefits by interacting with lipopolysaccharide (LPS)-induced nitric oxide (NO) production and iNOS expression.…”
Section: Anthranilic Acid Conjugated Phenolamidesmentioning
confidence: 97%